Port privatization in an international oligopoly - Noriaki Matsushima; Kazuhiro Takauchi (Osaka University, Institute of Social and Economic Research (ISER), 2013)
We investigate how port privatization affects port charges, firm profits, and welfare. Our model consists of an international duopoly with two ports and two markets. When the unit transport cost is large, privatization of ports decreases the prices for port usage, although neither government has an incentive to privatize its port. The equilibrium governmental decisions are inconsistent with the desirable outcome if the unit transport cost is not large enough. The smaller country's government is more likely to privatize its port, although the larger country's government is more likely to nationalize its port to protect its domestic market.
Keywords: L33; F12; R48; F13; 330; Port; Privatization; Port charge; Oligopoly; Strategic trade policy; Hafen; Privatisierung; Gebühr; Transportkosten; Strategische Handelspolitik; Oligopol; Theorie